An EH2‐mode microstrip leaky‐wave antenna with single beam radiation and backward‐to‐forward scanning. Issue 12 (22nd October 2022) - Liu, Runze; Wang, Henghui; Xu, Kuiwen; Sun, Sheng
Abstract: In this work, a leaky‐wave antenna (LWA) based on the second higher‐order‐mode (EH2 ‐mode) microstrip line is proposed for achieving the backward‐to‐forward beam scanning and single main beam radiation. The original microstrip EH2 ‐mode LWA inherently radiates two symmetric beams in the transversal plane. By loading a series of longitudinal slots, the dual‐beam radiation of the antenna is converted into single‐beam radiation. To achieve the continuous beam scanning, a series of transversal slots are further etched at each periodic cell correspondingly, where the frequency balanced condition could be satisfied for suppressing the open‐stop band. Finally, a prototype of the proposed EH2 ‐mode LWA is designed, implemented and fabricated. The measured results agree well with those results obtained from the simulation, validating the proposed method of single‐beam radiation and OSB suppression. The designed antenna in the measurement can scan from −15° to +15° with the frequency varying from 4.7 to 5.4 GHz.